SISTEM INFORMASI WEDDING PLANNER BERBASIS WEB - Ina Najiyah; Suharyanto Suharyanto (LPPM Nusa Mandiri, 2017)
Currently, wedding organizers are being sought after by prospective brides who want to realize their dream wedding. Therefore the bride must have information about the wedding organizer in order to choose the concept or things that are needed for the wedding. The Internet becomes the main way for the public in the search for information, one of the sources of such information is the website. The most sought-after information required is the wedding organizer. The number of wedding organizer websites is already very much so that the bride has many references, but if we have to open one by one website it will take a lot of time and not necessarily the things desired by the bride and groom is available in the WO. To solve the problem, we need a website that becomes a unifying place for all WO. The method used in making wedding planner website is planning, analysis, design, and implementation. A website wedding planner is made with a web-based program that can be accessed by anyone, anywhere, and anytime. Website Wedding Planner is designed with PHP and MySQL database. Making a wedding planner website is aimed to accommodate vendors or WO to promote products on the website more effectively and efficiently and can provide complete information for wedding planning for the bride and groom.